Clinical effects of air pollution on the central nervous system; a review - Babadjouni, Robin M.; Hodis, Drew M.; Radwanski, Ryan; Durazo, Ramon; Patel, Arati; Liu, Qinghai; Mack, William J. (Journal of clinical neuroscience, 2017)
•Clinical and epidemiological studies have established adverse effects of air pollution on the central nervous system.•Air pollution is associated with cognitive dysfunction, Alzheimer’s disease and Parkinson’s disease.•Air pollution is associated with structural brain effects and white matter injury.•Adverse outcomes in stroke and carotid artery disease are associated with air pollution.•This review examines the clinical effects of air pollution on neurological health. The purpose of this review is to describe recent clinical and epidemiological studies examining the adverse effects of urban air pollution on the central nervous system (CNS). Air pollution and particulate matter (PM) are associated with neuroinflammation and reactive oxygen species (ROS). These processes affect multiple CNS pathways. The conceptual framework of this review focuses on adverse effects of air pollution with respect to neurocognition, white matter disease, stroke, and carotid artery disease. Both children and older individuals exposed to air pollution exhibit signs of cognitive dysfunction. However, evidence on middle-aged cohorts is lacking. White matter injury secondary to air pollution exposure is a putative mechanism for neurocognitive decline. Air pollution is associated with exacerbations of neurodegenerative conditions such as Alzheimer’s and Parkinson’s diseases. Increases in stroke incidences and mortalities are seen in the setting of air pollution exposure and CNS pathology is robust. Large populations living in highly polluted environments are at risk. This review aims to outline current knowledge of air pollution exposure effects on neurological health.